Faktor Status Gizi Lebih Pada SiswaI di Madrasasah Ibtidaiyah Negeri 2 Johar Baru, Jakarta Pusat - Rahmani, Nur; Kumala Dewi, Gusti (Jurnal Gizi dan Kuliner, 2023)
Overnutrition status is one indicator that describes a person’s nutritional needs being met. Data related to obesity from the Ministry of Health of the Republic of Indonesia (2018), at the age of 5-12 years is still high, and with the highest prevalence in DKI Jakarta. This study aims to identify factors that can affect the nutritional status of students at MIN 2 Johar Baru. The research was carried out using a cross-sectional design, and purposive sampling technique involving 49 students in grades IV, V, and VI in July 2021. The data was obtained using an online questionnaire which was filled in by the respondents themselves. Statistical analysis using chi-square test. The results showed that as many as 48,1% of respondents experienced more nutritional status. Bivariate results using the chi-square test found a significant relationship between gender on overweight status (p = 0,000). There was no significant relationship between age (p = 0,978), last education of parents (father) (p = 547), last education of parents (mother) (p = 0,174), physical activity (p = 0,903), watching television (TV) (p = 0,303), and consumption of fast food (p = 0,846) on overweight status. Keywords: Nutritional Status, Physical Activity, Consumption of Fast Food